Emergency zero-fluoroscopy catheter ablation for refractory ventricular tachycardia in third-trimester pregnancy: a case report - Liu, Guiying; Quan, Shuping; Chen, Xiongbiao; Zhang, Xianyou (Frontiers in Cardiovascular Medicine, 2025)
BackgroundThe incidence of symptomatic arrhythmias during pregnancy has markedly increased in recent years. Atrial fibrillation/flutter and life-threatening ventricular arrhythmias are of particular concern due to their association with elevated maternal and fetal risks. Cardioversion, antiarrhythmic drugs, or catheter ablation are treatment options for hemodynamically unstable arrhythmias. However, indications of therapeutic options and standardized protocols remain scarce due to the limited shared clinical experiences and evidence.Case summaryOn 17 June 2025, our team managed a 32-week pregnant patient with refractory ventricular tachycardia (VT) following a 16-day treatment course for myocarditis. The arrhythmia was unresponsive to intravenous adenosine. After multidisciplinary evaluation, the condition was attributed to idiopathic VT. Emergency transcatheter cardiac radiofrequency ablation was performed with zero fluoroscopy, achieving immediate rhythm control without recurrence. Perioperative care focused on monitoring for cardiac complications and fetal status through close collaboration among intensivists, electrophysiologists, cardiologists, obstetricians, and pediatricians. The patient was discharged 2 days post-ablation and delivered a healthy infant 2 months later.ConclusionThis case demonstrates the successful use of emergency zero-fluoroscopy radiofrequency ablation for drug-refractory VT in a third-trimester pregnancy. It highlights the importance of including idiopathic VT in the differential diagnosis of unexplained troponin elevation and underscores the value of multidisciplinary care and shared decision-making.